Effect of Tool Rotation Speed on Mechanical Properties and Microstructure as the Results of Friction Stir Welding Method on Aluminium 5083-7075 - Maryati Maryati; Bambang Soegijono; M Yudi Masduky; Tarmizi Tarmizi (Institut Teknologi Bandung, 2016)
Friction Stir Welding (FSW) is a new method of welding process which is affordable and provide good quality. Aluminium 5083-7075 has been connected successfully by using friction stir welding (FSW) method into butt joint connection form. Tool rotation speed is one of the important parameters in FSW. The changes of rotation speed will affect the characteristics of mechanical properties and microstructure. The parameters of welding being used are welding speed of 29 mm/minutes by varying the speed rotation of 525 rpm, 680 rpm, 910 rpm, and 1555 rpm. In order to find out the mechanical strength of welds, tensile strength and hardness testing is done while finding out the microstructure will be done by using optical microscope and Scanning Electron Microscope (SEM). The result of the research showed that the highest tensile strength obtained at 910 rpm speed rotation about 244.85 MPa and the greatest hardness values was found on aluminium 5083 around the wheel zone area about 96 HV with rotary speed of 525 rpm. Then, the result of testing the macro and microstructure on all samples indicated defect which is seen as incomplete fusion and penetration causing the formation of onion rings. In other words, it is which showed that the result of stirring and tacking in the welding area is less than perfect.